(untitled) (Società e diritti, 2024)
The Code of the Third sector has required civilly recognized ecclesiastical bodies to fulfill additional obligations with respect to non-confessional entities. Its incomplete discipline has given rise to innumerable interpretative difficulties and consequent doubts on the systematic placement of the various legal institutions. In particular, the fulfillments, that are directed to religious entities, to constitute a destined patrimony, without further specifications in this regard by the law, leads to considerations on the nature of the patrimonial bond and on the delimitation of the resources necessary to carry out an activity of general interest. In any case, all the analyses must preserve the confessional nature of ecclesiastical bodies, in harmony with the constitutional principles set up to oversee religious Confessions